Functional magnetic resonance connectivity studies in infants born preterm: suggestions of proximate and long‐lasting changes in language organization. (March 2016) - Kwon, Soo Hyun; Scheinost, Dustin; Vohr, Betty; Lacadie, Cheryl; Schneider, Karen; Dai, Feng; Sze, Gordon; Constable, R Todd; Ment, Laura R
Abstract : Sophisticated neuroimaging strategies demonstrate alterations in functional connectivity at school age, adolescence, and young adulthood in individuals born preterm. Recent data suggest these alterations are present in the postnatal period prior to term‐equivalent age in neonates born preterm. Likewise, functional organization increases across development, but the influence of preterm birth on this fundamental infrastructure is immediate and unchanging. This article briefly reviews the current methods of measuring functional connectivity throughout development in those born preterm, and the association of functional connectivity with language disorders. Taken together, these data suggest that the effects of preterm birth on the functional organization of language in the developing brain are both proximate and long‐lasting. What this paper adds: Preterm birth alters functional organization in developing brain. These changes occur early in life, prior to term‐equivalent age. Alterations in neural networks correlate with language testing scores in childhood, adolescence and adulthood. These alterations in connectivity are both proximate and long‐lasting.